Hot corrosion behaviour of austenitic steel-308 in chloride salts / Mohd. Misbahul Amin, Che Mohd. Ruzaidi Ghazali and Neelofar Amin - Amin, Mohd. Misbahul; Ghazali, Che Mohd. Ruzaidi; Amin, Neelofar (2008)
The intensification of process engineering in almost every branch of modern technology, and development of new technologies make increasingly higher requirements for metallic construction materials, especially for their heat and scaling resistance. The increase in operating efficiency of certain installation or plants is generally achieved by the application of higher temperatures and pressures and higher flow velocities of gases and vapors which creates gas corrosion hazard for the construction materials. The hot corrosion behavior of Austenitic steel-30B in presence of chloride salts at 950° C in a slow current of air for the period of 72 hours has been studied. The Austenitic-308 alloy were severely attacked by calcium- and barium-chlorides due to formation of volatile metallic chlorides. The data have been complemented by oxidation kinetics measurements and morphological structures were analyzed using scanning electron microscope (SEM). The elemental distribution on the alloy surface deposits were characterized by using energy dispersive X-ray analysis (EDAX) techniques. The alkaline earth metal chloride salts have deleterious effect on the protectivity of the scales and rapid degradation of the alloy is noted.